The effect of commitment level in foundations that are non-profit organizations on employee motivation - Korkmaz, Aslı (My University, 2005)
Çalışanların örgüte bağlılıkları çalışanın kendisini, çalıştığı örgütü ve aynı zamanda toplumu etkiler. Çalışanlar örgüte ne kadar çok bağlanırlarsa, o derece az örgütten ayrılma davranışı sergilerler. Bu durumda örgüte devamlılıkları yüksek olacaktır. Diğer taraftan, örgüte bağlılık iş gücü dönüşüm oranını (hareketliliğini) azaltmakta, ancak üretimi ve iş motivasyonunu arttırmaktadır. Bu araştırmanın amacı, vakıf çalışanlarının örgüte bağlılıklarının, içerik teorilerinden biri olan Maslow'un ihtiyaçlar hiyerarşisi yardımıyla motivasyonlarını belirlemektir. Uygulamanın temelini örgütsel bağlılığı etkileyen faktörlerden biri olan kişisel özellikler oluşturmaktadır. Employee's commitment to the organization has effects on the employees themselves, on the organization and on society. As employees become more committed, they show reduced withdrawal behaviors and increased citizenship behaviors in their organizations. On the other hand, employee's commitment brings decreased amount of job movement, greater productivity and motivation. This research mainly aims at determining the motivation degree of Foundation employees with utilization of the concepts in one of the content theories of motivation, the need hierarchy theory, which has been conceptualized by Maslow. The present study attemps to investigate the relationship between employee's commitment level and their job motivation. Basic of the application is personal characteristics which is the one part of the organizational commitment in antecedents.
Keywords: Örgütsel Davranış